Ethics and Governance in the Time of Ramayana - Ruchie Sah; Mridu Sah (Yayasan Rumah Peneleh, 2021)
This paper employs the epic story of Ramayana for having better understanding of good governance, leadership and strategies for development of organization. Good governance is basic requirement for maintaining peace and harmony in any society. However, good governance has become a rarity in today’s world. A large majority of political, business and other leaders are increasingly engaged in self -serving pursuits of personal glorification and enrichment. By realizing significance of Ramayan for good governance and leadership, young generation can learn from history and this will encourage various management teachers to develop indigenous case studies based on similar incidences to bring new ideas into management discipline. The practicing managers can find new ideas and strategies for their development and their organisational development.